Tumor-Derived cGAMP Regulates Activation of the Vasculature - Campisi, Marco; Sundararaman, Shriram K.; Shelton, Sarah E.; Knelson, Erik H.; Mahadevan, Navin R.; Yoshida, Ryohei; Tani, Tetsuo; Ivanova, Elena; Cañadas, Israel; Osaki, Tatsuya; Lee, Sharon Wei Ling; Thai, Tran; et al. (Frontiers in Immunology, 2020)
Intratumoral recruitment of immune cells following innate immune activation is critical for anti-tumor immunity and involves cytosolic dsDNA sensing by the cGAS/STING pathway. We have previously shown that KRAS-LKB1 (KL) mutant lung cancer, which is resistant to PD-1 blockade, exhibits silencing of STING, impaired tumor cell production of immune chemoattractants, and T cell exclusion. Since the vasculature is also a critical gatekeeper of immune cell infiltration into tumors, we developed a novel microfluidic model to study KL tumor-vascular interactions. Notably, dsDNA priming of LKB1 reconstituted tumor cells activates the microvasculature, even when tumor cell STING is deleted. cGAS-driven extracellular export of 2’,3'-cGAMP by cancer cells activates STING signaling in endothelial cells and co-operates with type 1 interferon to increase vascular permeability and expression of E selectin, VCAM-1, and ICAM-1 and T cell adhesion to the endothelium. Thus, tumor cell cGAS-STING signaling not only produces T cell chemoattractants, but also primes tumor vasculature for immune cell escape.